2011
DOI: 10.1371/journal.pone.0020464
|View full text |Cite
|
Sign up to set email alerts
|

Association Between TAS2R38 Gene Polymorphisms and Colorectal Cancer Risk: A Case-Control Study in Two Independent Populations of Caucasian Origin

Abstract: Molecular sensing in the lingual mucosa and in the gastro-intestinal tract play a role in the detection of ingested harmful drugs and toxins. Therefore, genetic polymorphisms affecting the capability of initiating these responses may be critical for the subsequent efficiency of avoiding and/or eliminating possible threats to the organism. By using a tagging approach in the region of Taste Receptor 2R38 (TAS2R38) gene, we investigated all the common genetic variation of this gene region in relation to colorecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
91
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 46 publications
7
91
2
Order By: Relevance
“…1). The increased frequency of AVI/AVI carriers in patients and increased cancer risk for AVI/ AVI genotype have been reported in German and Czech populations for colorectal cancer (29) and our present analysis confirmed the result in a Japanese population. Increased frequencies of AVI/AVI carriers was also suggested for some cancer subtypes although they were not statistically significant; AVI/AVI frequency for biliary tract cancer was 29% (n55), that for hepatocellular carcinoma was 50% (n51), that for pancreatic cancer was 19% (n54), that for colorectal cancer was 33% (n57) and that for gastric cancer was 28% (n55).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…1). The increased frequency of AVI/AVI carriers in patients and increased cancer risk for AVI/ AVI genotype have been reported in German and Czech populations for colorectal cancer (29) and our present analysis confirmed the result in a Japanese population. Increased frequencies of AVI/AVI carriers was also suggested for some cancer subtypes although they were not statistically significant; AVI/AVI frequency for biliary tract cancer was 29% (n55), that for hepatocellular carcinoma was 50% (n51), that for pancreatic cancer was 19% (n54), that for colorectal cancer was 33% (n57) and that for gastric cancer was 28% (n55).…”
Section: Resultssupporting
confidence: 91%
“…We showed that homozygous TAS2R38 AVI/AVI carriers exhibit a higher cancer risk than carriers with other genotypes, supporting the previous observation in colorectal cancer patients by Carrai et al (29). It was also suggested in this study that homozygous TAS2R38 PAV/PAV carriers exhibit a lower cancer risk than carriers with other genotypes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…[1][2][3] Many bitter tastes come from healthy, plant-based phytochemicals such as isothiocyanates in cruciferous vegetables, 4 and the consumption of certain bitter foods can mitigate some chronic disease risks, but the desire to consume these bitter foods (e.g., coffee, cruciferous vegetables) is shaped by experiential, cognitive, and cultural influences as well as geneticallylinked bitter taste sensitivity. The gene that codes for the taste receptor member 38 protein (TAS2R38) is one of a family of bitter taste receptor genes found in the gustatory cells within the papillae of the tongue.…”
Section: Introductionmentioning
confidence: 99%